DIGITAL VILLAGE TELEVISION AS GOVERNMENT PUBLIC RELATIONS MEDIA TO DISSEMINATE INFORMATION - Farhan, Raihan; Sunuantari, Manik (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2023)
The gap in information dissemination is one of the problems that befell the people in Batu City. In 2020, the Ministry of Communication and Informatics’ service (Diskominfo) and KIM of Batu City formed 23 Digital Village Televisions named "TV Desa Kota Batu'' as media for information dissemination between stakeholders and the people. This research uses PENCILS theory and is a case study research. Data was collected through open interviews with figures who played significant roles in the program. The results showed that the TV Desa program was used as a medium of communication between the government and the people of Batu City. The Diskominfo and KIM of Batu City hold the role of Government Public Relations as facilitator, mediator, and collaborator. The dissemination carried out to KIM as a collaborator is empowerment through training. Meanwhile, information is disseminated to the people as the external public through many types of audio-visual content.